Male marriage squeeze and inter-provincial marriage in central China: evidence from Anhui - Liu, Lige (J Contemp China, 2013)
Since the 1990s, inter-provincial female migration for marriage has become important in central and eastern rural China. Using survey data from X County in rural Anhui Province, we explore the arrangement of inter-provincial marriages, as well as the characteristics of husbands and wives, marital satisfaction, and marital stability for these marriages. We find that inter-provincial marriage is an important option for local men to respond to the marriage squeeze and the increasing expense of marriage. It helps to relieve the shortage of marriageable women in the local marriage market. Because this kind of marriage is based on economic exchange, but not affection, it is often subject to a higher risk of marriage instability, and can lead to such illegal behaviors as marriage fraud and mercenary marriage.